Personal Digital Life Coach for Physical Therapy - Popovski, Goce; Ponciano, Vasco; Marques, Gonçalo; Pires, Ivan Miguel; Zdravevski, Eftim; Garcia, Nuno M (IEEE, 2020)
The functional tests are essential to test the functionality of different types of people, and specialty for older adults. The primary purpose of this paper is to create a method for the automatic measurement of the results of the different functional tests. These are the Heel-rise Test, Functional Reach Test, Timed Up and Go Test, Ten Meter Walk Test, Eight hop test, Up-down hop test, Side hop test, Single hop test, Chair Stand Test, Arm Curl Test, and Chair Sit and Reach test. The use of sensors may increase the accuracy of the measurements of these tests. These tests may identify several diseases, and it will be subject to further research in the future.
Keywords: Functional tests, physical therapy, mobile devices, automatic measurement, diseases